2010
DOI: 10.1002/pssb.200945234
|View full text |Cite
|
Sign up to set email alerts
|

Photo- and thermally stimulated luminescence of non-stoichiometric undoped PbWO4crystals

Abstract: Undoped PbWO 4 crystals prepared from non-stoichiometric melts, containing from 48.6 to 50.5 m% of PbO in the melt, were studied in the state as-grown, after annealing in air or in the Ar atmosphere, and after brushing away of the 50 mm thick surface layer of the annealed samples. Luminescence of these crystals was investigated at 80-300 K under selective excitation or after irradiation in the 3.5-5.0 eV energy range. Optically created defects were detected by the thermally stimulated luminescence (TSL) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…According to Ref. 16, these non‐stoichiometric crystals contain a large number of single oxygen and lead vacancies. Note that the position of the hole‐related TSL peak at ≈225 K is in agreement with the data obtained by ESR in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ref. 16, these non‐stoichiometric crystals contain a large number of single oxygen and lead vacancies. Note that the position of the hole‐related TSL peak at ≈225 K is in agreement with the data obtained by ESR in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous detailed studies of many different undoped and Mo‐doped PbWO 4 crystals have shown that mainly the recombination G(II) emission band peaking at 2.5 eV is observed in their TSL spectrum in the considered temperature range (see, e.g., 6, 9, 10, 14, 16–18). We assume that at 100–300 K, just the above‐mentioned non‐paramagnetic V Pb ‐related hole centers take part in the recombination processes accompanied with the G(II) emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of a composite TSL glow peak observed in [5,12] in the PWO:1200 ppm Mo, 80 ppm La crystal in the 170-250 K range requires further investigations. In previous studies carried out for different undoped and Mo-doped PWO crystals, all the TSL peaks in this temperature range were ascribed to the thermal destruction of various electron centers, e.g., Pb + -WO 3 centers [13], oxygen vacancy clusters with two trapped electrons [14][15][16], (MoO 4 ) 3centers [12,15], etc. In these TSL peaks, the green G(II) emission (2.5 eV, FWHM=0.55 eV [17]) is observed ascribed in [18] to the oxygen-deficient anion complexes in the form of WO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Lead tungstate crystal PbWO 4 , known as a scintillating crystal because of its high density, short radiation length, and fast decay time, has been widely investigated 5–9. PbWO 4 is a uniaxial crystal and belongs to the tetragonal system with space group of $C_{4h}^{6} {-} I4_{1} /a$ 10.…”
Section: Introductionmentioning
confidence: 99%